The first operation of the heavy ion beam probing diagnostic (HIBP) on the Uragan-2M torsatron - Zhezhera, A.I.; Chmyga, A.A.; Deshko, G.N.; Krupnik, L.I.; Kozachek, A.S.; Komarov, A.D.; Khrebtov, S.M.; Maznichenko, S.M.; Tashchev, Yu.I.; Lesnyakov, G.G.; Tarasov, I.K.; Perfilov, S.V. (Вопросы атомной науки и техники, 2015)
The Heavy Ion Beam Probing (HIBP) diagnostic system has been installed and operates now on the Uragan-2M torsatron for the first time in Ukraine. The cesium ion beam with energy range of 17…120 keV and ion current of 10…150 μA was used in the first experiments for tracing the probing beam through torsatron magnetic field (0.39…0.4 T). The secondary ion beam with intensity in the range of 30…100 nA was detected on the first deflecting plate of the secondary beam-line according to preliminary calculations by using 80 keV primary beam energy and 100 μA of primary ion current. The primary beam with energy range of 17…20 keV (Ibeam≈10 μA) was traced through torsatron magnetic field towards the analyzer detection plates.